Decoupling part geometry from microstructure in directed energy deposition technology : towards reliable 3D printing of metallic components - Yeoh, Yong Chen (Nanyang Technological University, 2021)
Directed energy deposition (DED) is an additive manufacturing technique that enables rapid production and repair of metallic parts with flexible geometry. However, the complex nature of thermal and material transport during DED can yield unwanted microstructure heterogeneity, which causes scatter in parts performance and hinders the adoption of DED technology by the industry. This heterogeneity can be exacerbated by the size and geometry of the build, as well as the deposition strategy employed. In this thesis we aim at unveiling these complex process-structure-property relationships to enable the production of DED parts with controlled microstructure and consistent properties. The first part (see chapter 4) of this thesis focuses on developing a set of DED process parameters for the deposition of I718. Using a design of experiment approach, we investigate what parameters yield full-density builds and how the build quality changes as a function of the geometry of the printed specimens. We find that the laser power is the most important parameter to control the size of bead, while the powder feeding rate is critical for bead height. Using this knowledge, we produce a series of specimens that we use in the second part of the thesis to investigate the resulting microstructure. In the second part (see chapter 5 and 6), we investigate microstructure variations at different length scales in the produced specimens. We quantify spatial trends in grain structure, texture, composition, and solidification structure within parts and correlate them with variations in hardness, yield strength, and Young’s Modulus to highlight the effect of the thermal environment during solidification. We find that the high energy input employed when using high deposition rates is conducive to significant microstructure heterogeneity along both the build and transversal directions, which stems from the asymmetric cooling rates generated by the deposition strategy used. Using these findings, in the third part (see chapter 7) of the thesis we demonstrate the ability to produce the desired microstructures through careful selection of process parameters. High thermal input results in strong <100> texture along building direction and enhances micro-segregation during solidification, which results in formation of different phases across the build. Conversely, processes with low heat input are conducive to a reduced thermal built up and a more homogeneous microstructure. To further demonstrate the effect of thermal history on printed part microstructure, we study the effect of sample size using different set of process parameters. We find variation in dendrite spacing, grain size and grain orientation on parts with different geometry, despite the same process parameter employed. We also find that as-printed elemental segregation and distribution of secondary phase will directly influence heat-treated microstructure. In summary, the complex process-structure-property relationships in DED processes result in microstructure heterogeneity of the printed parts. This thesis provides insights into the root causes for the observed heterogeneity as well as possible approaches how to control it to achieve consistent builds. As such, these results have important implications and can serve as a useful reference for the development of process parameters with optimum build rate and desired microstructure.